The Use of Technology for Collaborative Writing: Using Google Drive and WhatsApp - Sabrawi, Sabrawi; Senowarsito, Senowarsito; Setyaji, Arso (Universitas PGRI Semarang, 2022)
The rapid development of technology has significantly impacted the way educators collaborate, providing numerous digital platforms that facilitate sharing ideas, developing plans, and evaluating outcomes. In Indonesia, however, the implementation of collaborative writing (CW) among teachers has received limited attention. This study aims to explore how Google Drive and WhatsApp can be effectively utilized to support collaborative writing among teachers. Google Drive was employed for planning, editing, writing, and revising collaborative papers, while WhatsApp served as a communication tool for interaction, negotiation, confirmation, and decision-making. The paper presents the findings of this collaborative process, focusing on the strategies and outcomes of using these applications in an educational context. The results demonstrate the potential of digital tools to enhance collaborative efforts among teachers, offering a model for improving collaboration in professional learning communities. This paper contributes to the understanding of technology-supported collaborative writing practices, particularly in the context of Indonesian education.